Illocutionary Acts Used in Hate Speech Comments on Zohran Mamdani’s Official TikTok Account - Aisyah, Siti Haifa Nur; Wardoyo, Cipto; Fauzi , Erfan Muhammad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Political discourses on TikTok frequently qualify by short and emotionally charged comments that may serve not just as statements of disagreement but also as forms of hate speech and communicative action. However, studies that have examined the association between hate speech forms and illocutionary act functions in political TikTok comments are relatively restricted. The research intends to identify the forms of hate speech and examine the illocutionary act functions discovered in comments on the official TikTok account of Zohran Mamdani. In this research a qualitative descriptive method with pragmatic approach and qualitative content analysis was applied. The data comprised of 67 selected public comments from ten movies on TikTok released in November 2025. The comments were purposively sampled based on hate speech indicators adopted from the Indonesian National Police Circular Number SE/6/X/2015 and examined using Searle’s theory of illocutionary acts. The results demonstrate four types of hate speech: insult, accusation/defamation, provocation and threat. The most dominant type was insult with (27 comments), followed by accusation/defamation (23 comments), provocation (14 comments) and threat (3 comments). The comments performed mainly expressive, forceful and directive acts as illocutionary functions. The results indicate that political comments on TikTok contain hate speech not just to express bad feelings but also to construct negative political images and influence the perspective of the audience. This research contributes to pragmatic studies by demonstrating how short political comments on TikTok function as significant communicative activities in the digital political discourse.